Perturbation of Thymocyte Development Underlies the PRRS Pandemic: A Testable Hypothesis - Butler, John E.; Sinkora, Marek; Wang, Gang; Stepanova, Katerina; Li, Yuming; Cai, Xuehui (Frontiers in Immunology, 2019)
Porcine reproductive and respiratory syndrome virus (PRRSV) causes immune dysregulation during the Critical Window of Immunological Development. We hypothesize that thymocyte development is altered by infected thymic antigen presenting cells in the fetal/neonatal thymus that interact with double-positive thymocytes causing an acute deficiency of T cells that produces “holes” in the T cell repertoire allowing for poor recognition of PRRSV and other neonatal pathogens. The deficiency may be the result of random elimination of PRRSV-specific T cells or the generation of T cells that accept PRRSV epitopes as self-antigens. Loss of helper T cells for virus neutralizing (VN) epitopes can result in the failure of selection for B cells in lymph node germinal centers capable of producing high affinity VN antibodies. Generation of cytotoxic and regulatory T cells may also be impaired. Similar to infections with LDV, LCMV, MCMV, HIV-1 and trypanosomes, the host responds to the deficiency of pathogen-specific T cells and perhaps regulatory T cells, by “last ditch” polyclonal B cell activation. In colostrum-deprived PRRSV-infected isolator piglets, this results in hypergammaglobulinemia, which we believe to be a “red herring” that detracts attention from the thymic atrophy story, but leads to our second independent hypothesis. Since hypergammaglobulinemia has not been reported in PRRSV-infected conventionally-reared piglets, we hypothesize that this is due to the down-regulatory effect of passive maternal IgG and cytokines in porcine colostrum, especially TGFwhich stimulates development of regulatory T cells (Tregs).